Body mass and kicking velocity is significantly correlated to front kicking, but not roundhouse kicking performance in amateur male kick boxers. - Del Vecchio, L.; Stanton, R.; Davis, P.; Reaburn, P. (Journal of Australian Strength and Conditioning, 2017)
Despite the increasing popularity of kickboxing and associated combat sports, no studies to date have examined field-based performance tests that may influence roundhouse and front kicking performance. The aim of the present study was to investigate the relationships between field-based measures of mean kicking velocity, lower limb strength, lower limb power, and mean front and roundhouse kicking impact power. A cross-sectional study design assessed the following variables: anthropometrics, mean kicking velocity, single-leg isometric strength, single-leg jumping power, and both roundhouse and front kick impact power. Ten amateur male kickboxing athletes (30.7 ± 9.2 yrs., 178.6 ± 0.6 cm, 82.9 ± 8.3 kg) performed repeated trials of front and roundhouse kicking to determine velocity and impact power followed by single leg strength and single leg countermovement jump tests. Significant bivariate correlations were observed between preferred leg front kick impact power and body mass (r=0.75, p<0.05) and between preferred stance leg front kick impact power and kicking velocity (r=0.80, P<0.05). The results of this study suggest both single leg isometric strength and single leg countermovement jump power do not influence front or roundhouse kicking impact power. Therefore, strength and Conditioning coaches should prioritize the technical aspects of kickboxing training, when working to improve front and roundhouse kick performance.